Empowering Students through Health Literacy: A School-Based Community Learning Innovation in Secondary Education - Emy Leonita; Yuda Irawan; Nopriadi Nopriadi; Oktavia Dewi (AL-ISHLAH: Jurnal Pendidikan, 2025)
Adolescents are increasingly at risk of preventable health issues due to unhealthy lifestyle behaviors and limited access to contextualized health education. Addressing this gap, the study aimed to develop and evaluate a School-Based Community Learning Model that enhances health literacy and student engagement through participatory, project-based learning. The intervention was based on contextual teaching, social constructivism, and experiential learning principles. It involved digital health modules, peer discussions, and community action projects delivered over six weeks to 120 senior high school students in Pekanbaru, Indonesia. A quasi-experimental pretest-posttest control group design was employed to assess changes in health literacy and life skills. Statistical analysis showed a significant improvement in both health literacy and life skills in the intervention group (p 0.001). The average N-Gain score was 0.62, indicating moderate-to-high learning gains. Qualitative observations also indicated enhanced collaboration, critical thinking, and student initiative—markers of affective and psychomotor development. These findings suggest that the model effectively fosters essential health competencies and supports holistic student development. By aligning with national education goals, the program provides a viable framework for integrating health education into the standard curriculum. The School-Based Community Learning Model presents a scalable and practical approach to embedding health literacy in secondary education. It reinforces the role of health education as a fundamental aspect of character building and life skills development in schools.